Analysis of international scientific production on the theme of the use of essential oils in phytopathogenic bacteria (Research, Society and Development, 2020)
Agricultural production worldwide is affected by various types of diseases caused by bacteria, which can reduce the quantity and quality of production, thus the use of products harmful to human health has become common practice for the production and supply of food for the population. In view of this scenario, society is faced with the challenge of increasing the availability of food and reducing the use of pesticides, which cause damage to the environment and the well-being of the population. Given the above, the study aimed to analyze the international scientific production on the theme of the use of essential oils in the control of phytopathogenic bacteria, through the use of bibliometrics. The Web of Science and Scorpus databases were used, in addition to the Vantage Point software for organizing and processing data from February 20 to March 20, 2018. Using the generalized search, without specifying phytopathogenic bacteria, there was response of 10343 articles in the databases, with the specification there was a return of 111 publications. The related research area in the two databases with the largest publications was Chemistry, totaling 37 articles (33% of the total sample). Among the countries with the largest number of publications are: Peru; Italy, Tunisia and India in descending order. 276 different authors were identified, of which Tunisia and Turkey were the ones who produced the most on both bases. Scientific production continues with a low rate of publications, research in the area of bacterial control has shown an important, but discreet growth in recent years when compared to the control of phytopathogenic bacteria.